Analisis Konjoin Sebagai Preferensi Konsumen Terhadap Pemilihan Produk T-Shirt Wanita Bergaya Korea: Indonesia - Safina Ramadhani, Nadilla; Sienatra, Krismi (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This research aims to determine consumer preferences for the attributes of Korean-style T-shirt products which can be used for business development and marketing strategy planning in Korean-style T-shirt businesses. The research method used is a quantitative research method with a conjoint analysis approach. In this study, there are 16 stimuli that will be tested from the results of the orthogonal design. There are 5 attributes that produce this stimulus, namely: (1) Price, (2) Size, (3) Material, (4) Model, and (5) Color. The research results show that the first attribute considered important by consumers is the size attribute with a relative importance value of 32.297%. The second attribute that is considered important by consumers is the color attribute with a relative importance of 26.014%. The third attribute that is considered important by consumers is the material attribute with a relative importance of 20,330%. The fourth attribute that is considered important by consumers is the price attribute with a relative importance value of 10.813%, and the fifth attribute is the model with a relative importance value of 10.519%. This research can be useful for similar businesses in understanding consumer preferences and can be applied to other fashion industries.